The Legal Regulation of Preventing Discrimination and Harassment in the Workplace: An Analytical Study - Raghad Fahd Al-Mutrafi; Amal Shalabi Khadragey (International Journal of Law Research and Studies, 2026)
This research examines the legal regulation of preventing discrimination and harassment in the workplace within the Saudi legal system. It discusses the concept of discrimination, the scope of its prohibition, and its various forms, particularly discrimination based on gender and disability. The study also highlights the extent of the Saudi legislator’s commitment to promoting the principles of equality and equal opportunities throughout all stages of the employment relationship, beginning with job advertisements and recruitment, continuing during employment, and extending to the termination of the employment relationship.The research further addresses the concept of workplace harassment and its different forms, whether verbal, non-verbal, or physical, while clarifying the legal and regulatory measures established by the Saudi legal system to combat harassment and behavioral misconduct in the workplace. The study concludes that the Saudi legislator has adopted an integrated preventive and punitive approach aimed at protecting the dignity of employees and promoting a safe work environment based on justice, respect, and equality.
Keywords: Discrimination; Workplace; Harassment; Saudi Labor Law; Equality; Equal Opportunities; Disability; Gender Discrimination; Legal Protection; Behavioral Misconduct